Role of consolidation with yttrium-90 ibritumomab tiuxetan in patients with advanced-stage follicular lymphoma - Sánchez Ruiz, Antonio C. (SAGE Publications, 2014)
Non-Hodgkin’s lymphoma (NHL) accounts for 4% of all cancers diagnosed in the United States. Follicular lymphoma (FL) is the most common type of indolent NHL with a survival from 5 to 15 years. Although it is very sensitive to chemotherapy and radiotherapy, relapses are the main cause of therapeutic failure, and currently there is no consensus on the first-line treatment and optimal therapeutic strategies for patients with FL. Immediate treatment offers any survival benefit for asymptomatic and more indolent disease. In order to improve outcomes in FL, extend the remission, postpone the need for chemotherapy and improve OS, maintenance therapies with rituximab and consolidation treatments represent very attractive strategies. (90)Y-ibritumomab tiuxetan ((90)Y-IT, Zevalin®) is approval as consolidation therapy in previously untreated FL patients who achieve response to first-line chemotherapy. Consolidation therapy with (90)Y-IT after initial induction treatment has shown improved activity compared with induction chemotherapy alone, even in patients previously treated with rituximab, in one phase III and several phase II trials, improving progression-free survival (PFS) and rate of conversion from partial response (PR) to complete response (CR). The phase III international FIT trial shows an improvement in PFS that is maintained after a median follow up of 7.3 years. Several phase II trials show high rate of conversion from PR to CR and a significant improvement in PFS. Treatment is feasible and well tolerated although myelodysplastic syndrome cases has been observed in some trials. (90)Y-IT should be considered for the initial treatment of FL in patients who are unable to tolerate standard chemotherapy, e.g., elderly or frail patients and otherwise in high-risk patients who achieve a PR or CR due to improvements in CR rate and PFS.